CCR2+ Macrophages Promote Orthodontic Tooth Movement and Alveolar Bone Remodeling - Xu, Hao; Zhang, Shuting; Sathe, Adwait Amod; Jin, Zhichun; Guan, Jiani; Sun, Wen; Xing, Chao; Zhang, Hanwen; Yan, Bin (Frontiers in Immunology, 2022)
During mechanical force-induced alveolar bone remodeling, macrophage-mediated local inflammation plays a critical role. Yet, the detailed heterogeneity of macrophages is still unknown. Single-cell RNA sequencing was used to study the transcriptome heterogeneity of macrophages during alveolar bone remodeling. We identified macrophage subclusters with specific gene expression profiles and functions. CellChat and trajectory analysis revealed a central role of the Ccr2 cluster during development, with the CCL signaling pathway playing a crucial role. We further demonstrated that the Ccr2 cluster modulated bone remodeling associated inflammation through an NF-κB dependent pathway. Blocking CCR2 could significantly reduce the Orthodontic tooth movement (OTM) progression. In addition, we confirmed the variation of CCR2+ macrophages in human periodontal tissues. Our findings reveal that mechanical force-induced functional shift of the Ccr2 macrophages cluster mediated by NF-κB pathway, leading to a pro-inflammatory response and bone remodeling. This macrophage cluster may represent a potential target for the manipulation of OTM.